Cundaka: Analisis Gending Budhalan Wayang Kulit Purwa pada Sajian Pertunjukan Pakeliran Ki Purbo Asmoro - Pitutur Tustho Gumawang; Ryndhu Puspita Lokanantasari (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
The Javanese wayang kulit purwa (classical shadow puppetry) is a complex performance art form in which karawitan (gamelan music) plays a primary and crucial role, serving as accompaniment, building atmosphere, and accentuating the puppet's movements. A vital musical element within the pakeliran (puppetry performance) repertoire is the gending budhalan, a musical piece used to accompany the scene of a military departure. Ki Purbo Asmoro, one of the most influential dalang (puppeteers) of the contemporary pakeliran garap (interpretive performance style) era, is renowned for his intelligent and innovative performance concepts and musical interpretations. This study aims to analyze Gending Cundaka, a piece frequently used for this departure scene, within the context of Ki Purbo Asmoro's performances. Employing an ethnomusicological and performance studies approach, this qualitative research examines three main aspects: (1) the musical structure and aesthetics of Gending Cundaka; (2) its dramaturgical function as a gending budhalan; and (3) the uniqueness of Ki Purbo Asmoro's interpretation, or garap, that distinguishes his performances. Data were collected through participatory observation of Ki Purbo Asmoro's audio-visual performance recordings, transcription of musical arrangements, and a literature review. The findings indicate that in Ki Purbo Asmoro's interpretation, Gending Cundaka functions not merely as musical illustration but as a potent narrative instrument. Its assertive melodic structure, combined with dynamic kendhangan (drumming patterns) and dramatic tempo manipulations (seseg-kendho), effectively builds the performance's atmosphere, affirms the character of the troops, and provides psychological depth to the scene. The selection and treatment of this gending reflect Ki Purbo Asmoro's artistic intelligence in blending tradition with innovation to achieve gregel (an aesthetic thrill) and evoke a profound sense of rasa (deep feeling) in the audience.